Role of CB-NAAT in diagnosing extra pulmonary tuberculosis in correlation with FNA in a tertiary care center - Komanapalli, Sunil Kumar; Prasad, Uma; Atla, Bhagyalakshmi; Nammi, Vasundhara; Yendluri, Divya (International Journal of Research in Medical Sciences, 2018)
Background: The diagnosis of extra-pulmonary tuberculosis (EPTB) is challenging due to the pauci-bacillary nature of disease. Recently, WHO recommends GeneXpert/CBNAAT to be used as the initial diagnostic test in patients suspected extra-pulmonary tuberculosis (EPTB). The study was done to assess the role of Cartridge Based Nucleic Acid Amplification Test (CB-NAAT) in the diagnosis of EPTB. Aims and objectives was to study the role of FNAC, CBNAAT and Fluorescent LED in diagnosing extra-pulmonary tuberculosis (EPTB). Methods: This is a descriptive observational study carried out over a period of 12 months (April 2017 to March 2018) at department of Pathology, Andhra Medical College. All presumptive cases of extrapulmonary tuberculosis and purulent aspirates from the various sites between the age group of <10yrs to 60 years of age were included in the study. FNA was done and material sent to CBNAAT and fluorescent LED (Light-emitting Diode) microscopy in all the cases and results tabulated. Results: The total number of cases with presumptive extra pulmonary Tb were 289. Majority of the aspirates are from lymph nodal and cervical swellings 94.1% (272/289). CBNAAT has detected 6.5 % of cases (19/289) which were not detected by FNA and 9.3% of cases (27/289) LED negative cases. Resistant to rifampicin was identified in 2.1% (3/142 cases) of CBNAAT positive cases. Conclusions: FNA still remains the cheapest test to diagnose TB. In cases with Granulomatous lymphadenitis and purulent aspirates CBNAAT has an important role in diagnosing EPTB. In addition it offered rapid detection of rifampicin-resistant M. tuberculosis strains which is an added advantage.